Frequency study of functionally graded multilayer graphene platelet-reinforced polymer cylindrical panels - Farsadi, T.; Asadi, D.; Kurtaran, H. (Archives of Mechanics, 2021)
In this study, nonlinear fundamental natural frequencies of Functionally Graded (FG) multilayer Graphene Platelet-reinforced Polymer Composite (GPL-RPC) curved cylindrical panels are studied. It is considered that the Graphene Platelet (GPL) nanofillers are distributed in the matrix either uniformly or nonuniformly along the thickness direction. Four GPL distribution patterns namely, UD, FG-O, FG-X, and FG-A are considered. The effective material properties of GPL-RPC layers are obtained via the modified Halpin–Tsai micromechanics model and the rule of the mixture. A nonlinear structural model is utilized based on the virtual work principle. Green’s nonlinear kinematic strain relations are used to account for the geometric nonlinearities and the First-order Shear Deformation Theory (FSDT) is adopted to generalize the formulation for the case of moderately thick cylindrical panels including transverse shear deformations. The Generalized Differential Quadrature (GDQ) method of solution is employed to solve the nonlinear governing equations of motion. The present study aims to study the effect of GPL weight fraction for the proposed distribution patterns on the nonlinear fundamental frequency of functionally graded GPL-RPC cylindrical panels with different boundary conditions.